Penerapan Penilaian Persediaan Dan Perhitungan Harga Pokok Makanan Dengan Metode Fifo Pada Aplikasi Berbasis Web - Gabriella Dwi Ayuni; Magdalena Karismariyanti (Labkat Press KA FTIK UNIKOM, 2019)
The cost of food involved food consumed whereas labor costs and overhead costs were excluded. Both excluded costs were charged to various department. The value of the cost-of-food-sold shown in the food cost report, can be used as a reference to improve operational efficiency and take corrective actions. The value of the cost of foods consumed can be directly obtained from the inventory card using the First In First Out (FIFO) Method. The FIFO method calculated the actual cost of goods from the value of the goods themselves. In a foodservice industry, control of food supplies was an important activity, because inventory is one of the current assets nonetheless it is perishable. Moreover, inventory related transactions that had huge volume daily recorded unsystematically, can cause trouble with different amount between physical inventory checking and reports. Based on the weaknesses of the recording process, document flow analysis was carried out. Document flow analysis was used as a reference for developing web-based applications. This application was able to handle purchasing, delivery of food items from the purchasing department to the kitchen section, pick up of food ingredients for kitchen/meeting/promotion purposes, physical adjustment of inventory and displaying inventory cards and cost of food report.